Political parties and their online platforms–Differences in philosophies - Fitzpatrick, Jasmin; Thuermer, Gefion (Frontiers in Political Science, 2023)
As external forces seek to gain influence over ICTs of political parties, their security becomes an additional relevant factor in parties' finances. While many studies focus on parties' online fundraising, their spending for web-based technologies remains terra incognita. Our perspective follows the idea that a party's spending is an indicator for relevance. What aspects are on the table when new ICTs are purchased by parties? What significance do security concerns have? We analyzed the Green Parties in Germany and Austria. Both are forerunners in their use of online participation platforms with decades of experience in engaging members offline. We conducted interviews with stakeholders from both parties and an external IT-specialist. Our findings indicate differences in the approach of securing ICTs even among these most similar cases: some see security as a long-term issue and invest in in-house solutions, others see security as a necessary expense and opt for external service providers.